DNA Markers to Discriminate Cannabis sativa L. 'Cheungsam' with Low Tetrahydrocannabinol (THC) Content from Other South Korea Cultivars Based on the Nucleotide Sequences of Tetrahydrocannabinolic Acid Synthase and Putative 3-Ketoacyl-CoA Synthase Genes. (22nd November 2019) - Doh, Eui Jeong; Lee, Guemsan; Yun, Yeong-Jin; Kang, Lin-Woo; Kim, Eun Soo; Lee, Mi Young; Oh, Seung-Eun
Abstract : Cannabis sativa L. has been utilized for a long time as a traditional herbal medicine in Korea. Dry fruits, achenes, each containing a single seed of Cannabis, are currently prescribed as Ma In (Cannabis Semen), a laxative. As each achene is enclosed by a bract, in which tetrahydrocannabinol (THC), the main psychological active compound in Cannabis is synthesized; achene is easily contaminated by THC from bract remnants. Therefore, it is safer to harvest achenes from Cannabis with a low THC content. Seeds of hemp, a low THC Cannabis, were recently classified as possible sources of new pharmacologically active compounds. Thus, a proper method to select appropriate Cannabis plants with low THC among cultivars in South Korea for medicinal purpose is necessary. As a result of cross-selection, Cannabis L. cultivar "Cheungsam" (CH) with the lowest THC content among cultivars cultivated in South Korea has been developed. In this study, we developed two DNA markers to reliably discriminate CH from other local cultivars with higher THC contents. We developed primer sets CHF3/CHR2 to amplify the 642 bp DNA marker of CH based on differences in the nucleotide sequences of the THCA synthase gene, which encodes a key enzyme in THC synthesis. We then developed a CHF1/CHR3 primer set to amplify the 401 bp DNA marker of CH based on the differences in both the content of very long chain fatty acids (VLCFs) and the sequence of the putative 3-ketoacyl-CoA synthase ( KCS ) gene encoding enzymes synthesizing VLCFs among local cultivars.